The War on the Squatters, 1920-1940: Hamilton's Boathouse Community and the Re-Creation of Recreation on Burlington Bay - Bouchier, Nancy; Cruikshank, Ken (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2003)
Abstract Working-class Hamiltonians responded to a local housing crisis by creating a boathouse community along the shoreline of Burlington Bay and Dundas Marsh. Leasing or simply squatting the land, they enjoyed access to good fishing and hunting, a clean place to live, and seclusion from the gaze of local police. The notorious reputation of a nearby hotel, the presence of transients in the area, and rough elements of working-class recreation, however, made the community a prime target for urban reformers. They saw it as an unsightly problem, standing in the way of their plans to create an aesthetically-pleasing, moral, and orderly city. The "war on the squatters" shows the ways in which urban planners, conservationists, and moral reformers sought to reshape the human and natural environment of the bay, often at the expense of working people. Residents who had enjoyed resource and recreational advantages of living on the margins of Hamilton society paid the price politically when reformers contested their use of the area's natural resources. Although they won limited sympathy, they did not have the economic, legal, or political resources to fight those who saw their community as an aesthetic and moral blot on Hamilton's waterfront.